2017
DOI: 10.1111/emip.12163
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Undefined Cut Scores With the Hofstee Standard‐Setting Method

Abstract: This article provides an overview of the Hofstee standard‐setting method and illustrates several situations where the Hofstee method will produce undefined cut scores. The situations where the cut scores will be undefined involve cases where the line segment derived from the Hofstee ratings does not intersect the score distribution curve based on actual exam performance data. Data from 15 standard settings performed by a credentialing organization are used to investigate how common undefined cut scores are wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The pass mark is derived by the modified Angoff method [14, 15], which estimates what proportion of just passing candidates will answer the question correctly. A post hoc correction of the pass mark is applied using the Hofstee compromise [16] and then the final pass mark is calculated. For more details visit https://www.mrcpuk.org/mrcpukexaminations/results/exam-pass-marks.…”
Section: Towards Harmonization and Fewer Barriers: The Ecnmentioning
confidence: 99%
“…The pass mark is derived by the modified Angoff method [14, 15], which estimates what proportion of just passing candidates will answer the question correctly. A post hoc correction of the pass mark is applied using the Hofstee compromise [16] and then the final pass mark is calculated. For more details visit https://www.mrcpuk.org/mrcpukexaminations/results/exam-pass-marks.…”
Section: Towards Harmonization and Fewer Barriers: The Ecnmentioning
confidence: 99%
“…1 A range of methods can be used to determine this point and are covered in several other papers. [2][3][4] In summary, however, most methods fall into three categories: norm-referenced (determined by the performance of the student group), criterion-referenced (pre-determined as an absolute cut-off point) and compromise methods (a compromise between the previous two methods is found). 4…”
Section: Introductionmentioning
confidence: 99%
“…Among the methods for performing standard setting, compromise methods are some of easiest methods to explain to panelists and they are among the quickest methods to implement. The fact that compromise methods are easy to explain and implement makes them an attractive option to evaluate or adjust cut scores, or as a secondary method that can be performed following a test‐centered or examinee‐centered approach (see Geisinger, 1991; Mills & Melican, 1987, 1988; Wyse & Babcock, 2017). In fact, a common pairing of standard‐setting methods in credentialing programs is to use either the modified Angoff or Bookmark method along with the Hofstee and/or Beuk methods (see The American Board of Family Medicine, 2011; National Board of Osteopathic Medical Examiners, 2016; O'Neill, Marks & Reynolds, 2005; Wendt & Kenny, 2007).…”
mentioning
confidence: 99%
“…Wyse and Babcock (2017) further explored undefined cut scores with the Hofstee method using data from 15 credentialing programs. They found that undefined cut scores were not a rare occurrence and that the Hofstee and Beuk methods tended to produce similar cut scores.…”
mentioning
confidence: 99%
See 1 more Smart Citation